Reservasi Area Parkir Berbasis Internet Of Things - tukadi - tukadi; Rahcman - Arief; Wahyu Arief Rosyadi (Universitas Islam Lamongan, 2020)
In this study, a parking area reservation application was designed and made to solve this problem. In this study an application was designed using the application of IoT (internet of things) with the Wemos microcontroller and the HCSR-04 ultrasonic sensor as the main component by integrating google maps fire. This system allows visitors to monitor the parking area to make reservations for a parking area. The results obtained from making a web application visitors can see the available parking area, and can reserve one of the parking areas through the parking area reservation application that has been made. Based on the results of observations that have been made from the results of sensor testing to the database, the average is 0.0049 ms. This shows the application can work in realtime.